Analysis of Students' Errors in Solving Word Problems Viewed from Mathematical Resilience - Haerani, Agus; Novianingsih, Khusnul; Turmudi, Turmudi (Universitas Muhammadiyah Mataram, 2021)
Many students in the world have difficulty in solving word problems, including students in Indonesia. TIMSS has shown that only eight percent of Indonesian participants are able to solve word problems, this result is hugely lower than the international average of 18 percent. One of the factors that cause students' errors in solving word problems is mathematical resilience. Thus, this study aims to analyze students' misconceptions in solving word problems viewed by their mathematical strength. This study was conducted for sixth-grade students in one of the elementary schools in Bandung. This study was qualitative descriptive research. In this study, there were four steps: selecting the word problems, answering the issues, filling out a mathematical resilience questionnaire, and interviewing. Students were encouraged to respond to a three-word question within 30 minutes, filling out a mathematical resilience questionnaire followed by the interview. This study showed that the students' errors in solving word problems were including comprehension, transformation, and process skill errors. Based on mathematical resilience, students with a low level of resilience predominantly carried out comprehension errors. In contrast, students with a moderate level of resilience more dominant made transformation errors. Meanwhile, students with high resilience completed more questions correctly, although several students seemed to have made process skills errors. This study's limitation is the data obtained online so that the respondents completed the instrument exceeds the given time. Further researches are suggested to conduct directly in the classroom to maximize the accuracy of the study.